All that glitters is not gold! Job insecurity and well-being in STEM research fellows: a latent profile analysis - Bacci, Giulia; Viotti, Sara; Bertola, Lara; Converso, Daniela; Loera, Barbara (Frontiers in Psychology, 2024)
Job insecurity is now one of the major stressors affecting well-being at work. In academia, researchers appear to be in the most precarious position. To explore the relationship between job insecurity and well-being at work, we analyzed a sample of research fellows belonging to STEM disciplines in Italy. Using a latent profile approach, we identified three “hidden” subgroups: “Safe & Sound”; “Safe not so Sound” and “Neither Safe or Sound.” Compared to previous studies, our results show that even within a population of STEM researchers that tends to have good levels of employability and mobility, there are subgroups of people characterized by greater job insecurity and low work commitment, who suffer from emotional exhaustion and cynicism at work level, i.e., more exposed to the risk of burnout.